Perspectives on warm conveyor belts - sensitivities to ensemble configuration and the role for forecast error - Pickl, Moritz (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2023)
Warm conveyor belts (WCBs) are weather systems that substantially modulate the large-scale extratropical circulation. As they can amplify forecast errors and project them onto the Rossby wave pattern, they are of high relevance for numerical weather prediction. This work elaborates on two aspects of WCBs in the context of ensemble forecasts: (1) sensitivities of WCBs to the representation of initial condition and model uncertainties, and (2) the role of WCBs for forecast error growth.